2008
DOI: 10.1590/s1516-14392008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation behavior of FeCr and FeCrY alloys coated with an aluminium based paint

Abstract: A variety of metallic components rely on properties that are specific to the alloy and its surface. Coatings have been extensively used to protect metallic surfaces from the aggressive effects of the environment to which it is exposed. In this investigation, the high temperature oxidation behavior of a FeCr and a FeCrY alloy coated with an aluminium based paint has been studied. The objective was to form the more resistant alumina surface layer on an aluminium free alloy. Aluminium based paint coated and uncoa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…The relatively weak peak at ∼2.2 keV should be assigned to elemental S, which is due to the remnant (NH 4 ) 2 S 2 O 8 . The peak at 6.5 keV is from the overlapping signals of Fe and Mn, as observed in previous reports on Fe–Mn composites. , Many elements have overlapping peaks (e.g., Ti Kβ and V Kα, Mn Kβ and Fe Kα) because the energy levels for different elements are too close to be distinguishable from each other. The atomic percentages of Fe and Mn are 2.4 at.…”
Section: Resultssupporting
confidence: 60%
“…The relatively weak peak at ∼2.2 keV should be assigned to elemental S, which is due to the remnant (NH 4 ) 2 S 2 O 8 . The peak at 6.5 keV is from the overlapping signals of Fe and Mn, as observed in previous reports on Fe–Mn composites. , Many elements have overlapping peaks (e.g., Ti Kβ and V Kα, Mn Kβ and Fe Kα) because the energy levels for different elements are too close to be distinguishable from each other. The atomic percentages of Fe and Mn are 2.4 at.…”
Section: Resultssupporting
confidence: 60%
“…Thus, in excess of 8% Al, the aspect of the oxide is not uniform, adherent and compact, the superficial layer containing very thin alumina whiskers. The choice of a correct aluminum content of the FeCrAl alloys must be correlated with the content of chromium, according to the equation:% Al = (40 -% Cr)/6 [6,7]. At the same time, the chromium content below 12% does not offer sufficient resistance to oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…12 In recent years a number of studies have been carried out to exploit the benefits of rare earth additions on oxidation behavior of chromium dioxide and alumina forming alloys. 13,14,[16][17][18][19][20][21] Most studies reporting the reactive element effect in chromium dioxide forming alloys were carried out at or below 800 °C. A limited number of studies have reported this effect at temperatures above 950 °C, probably attributable to formation of volatile CrO 3 .…”
Section: Introductionmentioning
confidence: 99%